Hadith #3755 - Sunan Abi Dawud - Abdul Salam bin Harb bin Salm al-Mala'i عبد السلام بن حرب بن سلم النهدي الملائي; Abu Khalid al-Dalani أبو خالد الدالاني الأسدي; Hameed bin 'Abdur Rahman حميد بن عبد الرحمن الحميري; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب (Sunan Abi Dawud)
Safinah AbuAbdurRahman said that a man prepared food for Ali ibn AbuTalib who was his guest, and Fatimah said: I wish we had invited the Messenger of Allah (ﷺ) and he had eaten with us. They invited him, and when he came he put his hands on the side-ports of the door, but when he saw the figured curtain which had been put at the end of the house, he went away. So Fatimah said to Ali: Follow him and see what turned him back. I (Ali) followed him and asked: What turned you back, Messenger of All
Grade: Hasan